2020
DOI: 10.1016/j.fct.2019.110916
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of mitochondrial DNA homeostasis in drug-induced liver injury

Abstract: Mitochondrial DNA (mtDNA) encodes for 13 proteins involved in the oxidative phosphorylation (OXPHOS) process. In liver, genetic or acquired impairment of mtDNA homeostasis can reduce ATP output but also decrease fatty acid oxidation, thus leading to different hepatic lesions including massive necrosis and microvesicular steatosis. Hence, a severe impairment of mtDNA homeostasis can lead to liver failure and death. An increasing number of investigations report that some drugs can induce mitochondrial dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 162 publications
(274 reference statements)
0
23
0
4
Order By: Relevance
“…As in our studies, EPAC2A was barely detectable; the observed protective effects of EPAC2 inhibition can be primarily attributed to EPAC2B, which is also localized at the mitochondria. Another explanation may be that under stress conditions such as DILI, EPAC2A expression may be induced due to changes in the methylation status of the gene (Gervin et al, 2017;Fromenty, 2020). Further studies on the differential expression and subsequent impact of EPAC proteins on functional responses in primary rat hepatocytes will be fascinating but are beyond the current manuscript's scope.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As in our studies, EPAC2A was barely detectable; the observed protective effects of EPAC2 inhibition can be primarily attributed to EPAC2B, which is also localized at the mitochondria. Another explanation may be that under stress conditions such as DILI, EPAC2A expression may be induced due to changes in the methylation status of the gene (Gervin et al, 2017;Fromenty, 2020). Further studies on the differential expression and subsequent impact of EPAC proteins on functional responses in primary rat hepatocytes will be fascinating but are beyond the current manuscript's scope.…”
Section: Discussionmentioning
confidence: 95%
“…If EPAC2A is low or absent in hepatocytes, this implies that the observed protective effects of EPAC2 can be attributed to EPAC2B which is also localized at the mitochondria. Another probable explanation is that under stress conditions such as DILI, EPAC2A expression may be induced due to changes in the methylation status of the gene (Gervin et al, 2017;Fromenty, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are still some uncertainties regarding the precise mechanisms whereby APAP overdose can induce liver injury, numerous studies pointed to a major role of cytochrome P450 2E1 (CYP2E1), at least in mice [2,6,7]. Indeed, this enzyme catalyzes the oxidation of APAP to Nacetyl-p-benzoquinone imine (NAPQI), a highly reactive metabolite inducing severe mitochondrial dysfunction at the respiratory chain level, overproduction of reactive oxygen species (ROS), c-jun N-terminal kinase (JNK) activation, mitochondrial permeability transition, ATP depletion and massive hepatocellular necrosis [8,9]. In human, CYP3A4 might be an important enzyme catalyzing NAPQI generation in addition to CYP2E1 [2,10].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Many drugs can impair mtFAO by different mechanisms including direct inhibition of mtFAO enzymes such as carnitine palmitoyltransferase 1 (CPT1) and different acyl-CoA dehydrogenases as well as direct impairment of MRC and OXPHOS [ 20 , 63 , 77 , 78 ]. OXPHOS can also be impaired indirectly by alteration of mitochondrial DNA (mtDNA) homeostasis such as inhibition of mtDNA replication or translation [ 20 , 77 , 79 ]. All these adverse effects are not mutually exclusive.…”
Section: How Can Drugs Be More Hepatotoxic In Mafld?mentioning
confidence: 99%
“…For instance, some drugs such as acetaminophen, amiodarone and tamoxifen can directly inhibit both mtFAO and MRC [ 20 , 77 , 78 ]. In addition, acetaminophen and troglitazone can impair MRC activity directly or indirectly through mtDNA depletion [ 77 , 79 ]. Finally, it should be mentioned that drug-induced inhibition of mtFAO could not only worsen pre-existing steatosis but also necrosis since this metabolic pathway is a major source of energy in hepatocytes [ 77 , 80 ].…”
Section: How Can Drugs Be More Hepatotoxic In Mafld?mentioning
confidence: 99%